Serum IGF-1 and IGFBP-3 Levels in Middle Aged Turkish Males: Relationships with Bone Mineral Density and Markers of Bone Turnover (Male Osteoporosis & IGF-1, IGFBP-3) - Original Investigation - Melek Sezgin; Burak Çimen; Arzu Kanık; İsmet As; Neslihan Erçetin; Nurgül Arıncı İncel; Günşah Şahin (Galenos Yayinevi, 2007)
Aim: The aim of this study was to determine whether circulating levels of insulin-like growth factor-1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) were associated with bone mineral density (BMD) and bone turnover markers in middle aged Turkish males. Patients and Methods: At the beginning, a total of 160 Turkish men aged between 35 and 65 years were included to this study. The final sample comprised of 112 men because 48 men were excluded from the study. BMD of the spine and the hip was measured with dual energy x-ray absorptiometry. After an overnight fasting, serum IGF-1, IGFBP-3, intact parathyroid hormone, 25-hydroxy vitamin D, osteocalcin, C-terminal telopeptide, calcium, phosphorous and alkaline phosphatase levels were measured. Urinary concentrations of calcium, phosphorous and creatinine were also estimated. Results: Twenty-one men (18.8%) had a bone mineral density of ≤ -2.5 SD (T score). There was a significant difference in IGF-1 levels between men with normal BMD and men with reduced BMD (132.5 ± 38.1 and 116.1 ± 40.6 respectively and p: 0.04). Serum IGF-1 levels were positively correlated with BMD of the lumbar spine (r: 0.28, p:0.006), but there was no correlation between IGFBP-3 and BMD of any sites tested. IGF-1, IGFBP-3 and BMD were not correlated with bone turnover markers except serum alkaline phosphatase level. Conclusion: Serum IGF-1 levels were lower in men with reduced BMD and positively correlated with BMD of the lumbar spine. Neither IGF-1 nor IGFBP-3 was correlated with bone turnover markers. Further studies of these factors in skeletal cells are needed to explain their role in the pathophysiology of idiopathic male osteoporosis. (From the World of Osteoporosis 2007;13:37-43)